Stress and Coping Strategies among Adolescent Girls Regarding Pubertal Changes: A Cross-Sectional Study in Selected Schools of Jabalpur City - Anju Bala Sahu (Indian Journal of Nursing Sciences, 2025)
Background: Pubertal transition involves significant physical and psychological changes, often leading to stress among adolescent girls. Their ability to cope with these changes plays a crucial role in shaping their long-term mental well-being. This study aimed to assess stress levels, coping strategies, their interrelationship, and associations with demographic factors among adolescent girls. Materials and Methods: A cross-sectional descriptive study was conducted among 300 school-going adolescent girls (aged 11–18 years) in Jabalpur using non-probability purposive sampling. Data were collected through a self-developed, validated stress questionnaire and a coping strategy scale. An information booklet was later provided. Data were analyzed using descriptive and inferential statistics. Results: Moderate stress levels were observed in 66% of girls aged 11–14 and 63% of those aged 15–18. Coping strategy usage was also substantial in both age groups, with 67% (11–14 years) and 51% (15–18 years) employing effective strategies. A negative correlation (r = –0.20) was found between stress and coping in younger adolescents, and a positive correlation (r = 0.70) in older adolescents. Significant associations were found between stress levels and demographic variables such as age, education, family type, and age at menarche. Conclusion: Adolescent girls commonly experience stress during pubertal changes, but many adopt coping strategies. Timely intervention through education and counseling, including tools like information booklets, can help mitigate stress and enhance healthy coping.